Knowledge Gaps in the Understanding of Antimicrobial Resistance in Canada - Kayley D. McCubbin; Kayley D. McCubbin; R. Michele Anholt; Ellen de Jong; Ellen de Jong; Jennifer A. Ida; Diego B. Nóbrega; John P. Kastelic; John M. Conly; John M. Conly; John M. Conly; John M. Conly; et al. (Frontiers Media S.A., 2021)
Current limitations in the understanding and control of antimicrobial resistance (AMR) in Canada are described through a comprehensive review focusing on: (1) treatment optimization; (2) surveillance of antimicrobial use and AMR; and (3) prevention of transmission of AMR. Without addressing gaps in identified areas, sustained progress in AMR mitigation is unlikely. Expert opinions and perspectives contributed to prioritizing identified gaps. Using Canada as an example, this review emphasizes the importance and necessity of a One Health approach for understanding and mitigating AMR. Specifically, antimicrobial use in human, animal, crop, and environmental sectors cannot be regarded as independent; therefore, a One Health approach is needed in AMR research and understanding, current surveillance efforts, and policy. Discussions regarding addressing described knowledge gaps are separated into four categories: (1) further research; (2) increased capacity/resources; (3) increased prescriber/end-user knowledge; and (4) policy development/enforcement. This review highlights the research and increased capacity and resources to generate new knowledge and implement recommendations needed to address all identified gaps, including economic, social, and environmental considerations. More prescriber/end-user knowledge and policy development/enforcement are needed, but must be informed by realistic recommendations, with input from all relevant stakeholders. For most knowledge gaps, important next steps are uncertain. In conclusion, identified knowledge gaps underlined the need for AMR policy decisions to be considered in a One Health framework, while highlighting critical needs to achieve realistic and meaningful progress.